Experimental observation of gray whale skull vibrations amplified in the bony hearing complex - Margaret A. Morris; Petr Krysl; John A. Hildebrand; Ted W. Cranford (Scientific Reports)
Abstract Mysticete whales have bilateral bony ear complexes (tympanoperiotic complexes) that amplify low frequency vibrations in proximity to their vocalization ranges. Understanding the functional mechanics would enable precise predictions of mysticete hearing sensitivity, which is currently unknown. We conducted experiments on a juvenile and an adult gray whale skull from deceased animals to measure the vibrational dynamics between the tympanic bullae and the skull. Relative motions between bullae and skull indicate sound transfer to the inner ear. For the juvenile, assessments were performed on (1) a 3D-printed plastic skull-replica, (2) the original skull after much of the soft tissue had been removed by dissection, and (3) the denuded skull after hydrogen peroxide was used to erode the remaining soft tissues. We excited vibrations in the juvenile skull underwater by projecting sound in a test pool, ranging from 170–1000 Hz. Additionally, we measured in-air vibrations of the plastic, denuded, and adult skulls using a mechanical shaker to drive vibrations anteroposteriorly (rostrum-to-tail) from 150–1000 Hz. The results consistently showed amplification of vibrations at the tympanic bullae compared to the base of the skull, demonstrating a mechanism by which low-frequency sound is transferred from the environment, through the skull, to the inner ear.